2014
DOI: 10.1148/rg.341135038
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Techniques for Dose Optimization in Abdominal CT

Abstract: Recent advances in computed tomographic (CT) scanning technique such as automated tube current modulation (ATCM), optimized x-ray tube voltage, and better use of iterative image reconstruction have allowed maintenance of good CT image quality with reduced radiation dose. ATCM varies the tube current during scanning to account for differences in patient attenuation, ensuring a more homogeneous image quality, although selection of the appropriate image quality parameter is essential for achieving optimal dose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Multiple prior studies have shown that iterative reconstruction techniques allow for dose reduction while preserving image quality in the adult populations undergoing abdominal or thoracic CT imaging [11][12][13][14]. Based on the existing literature, MBIR has allowed greater dose reductions than ASiR in both children and adults [7,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prior studies have shown that iterative reconstruction techniques allow for dose reduction while preserving image quality in the adult populations undergoing abdominal or thoracic CT imaging [11][12][13][14]. Based on the existing literature, MBIR has allowed greater dose reductions than ASiR in both children and adults [7,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…6,12,13 In addition, IR algorithms can help reduce artifacts caused by metallic implants, as well as those resulting from photon starvation and beam-hardening effects. 1 It is therefore essential to understand how IR algorithms work in general, since it provides the basis to comprehending why IR algorithms are able to offer these advantages.…”
Section: Advantages Of Ir Algorithms and How They Workmentioning
confidence: 99%
“…The output is the resultant volumetric image after the termination of the iterative cycle. 1,6,9 The entire iterative reconstruction process is illustrated in Figure 2. A comparison of images reconstructed using the FBP and IR algorithms is shown in Figure 3.…”
Section: Advantages Of Ir Algorithms and How They Workmentioning
confidence: 99%
See 2 more Smart Citations